50+(6x-2)=180

Simple and best practice solution for 50+(6x-2)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 50+(6x-2)=180 equation:


Simplifying
50 + (6x + -2) = 180

Reorder the terms:
50 + (-2 + 6x) = 180

Remove parenthesis around (-2 + 6x)
50 + -2 + 6x = 180

Combine like terms: 50 + -2 = 48
48 + 6x = 180

Solving
48 + 6x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-48' to each side of the equation.
48 + -48 + 6x = 180 + -48

Combine like terms: 48 + -48 = 0
0 + 6x = 180 + -48
6x = 180 + -48

Combine like terms: 180 + -48 = 132
6x = 132

Divide each side by '6'.
x = 22

Simplifying
x = 22

See similar equations:

| B=-9x-3x | | -14(2x-10)=28 | | 4a-3=15 | | 5x+5=8x-9 | | -5p+5+6p=10 | | Ep+q=29 | | f(x+3)=x^2+5x+3 | | M=-4x+9z-9+2x-2z+4 | | 2(x-5)=3(5x+1) | | 9x-4=52-5x | | x^4-3x^3+4x+1=0 | | B=6x+3a-9+7x-8a+2 | | 4x-7+9x+13-5x-4= | | 6*x+x=63 | | 27=y-11 | | 3/(1-sqr19) | | 7x+17x+3y=180 | | 6(2x+3)=3(6x+4) | | 0/0=1 | | -(x/2) | | 2x-(2x+9)-6=-4x-6(-9-x)+2 | | U=7x+6b-5+2x-6b+4 | | 4y=120 | | (p^5/p^3)^6 | | 12m=9 | | 3x^2+6y^2=18 | | 5x-11=2(x+2) | | J=11-2.5(1.56) | | Z+-4x=2y | | y^3+2x=x-1 | | (8+2i)(5-9i)= | | -36+4x=12 |

Equations solver categories